(untitled) (Revista revoluciones, 2022)
In the following article, he proposes an epistemic-methodological model for the interpretation of philosophical texts, based on the textual philosophy of Paul Ricoer. The study used documentary research that aims to develop a conceptual theoretical framework to form a body of ideas about the object of study and discover answers to certain questions through the application of documentary procedures. The model consists of two axes: an epistemic one where resides all the philosophical rationality on the basis of the hermeneutics worked by Ricoeur. A second axis: methodological, from where Ricoeur’s experience is summarized and synthesized in relation to the procedure applied in the interpretation of texts. Regarding the procedure, the proposal is based on textual hermeneutics and inspired by mimesis, that is, the application of mimetic states: pre-comprehension or prefiguration, compression or configuration, and re-comprehension or refiguration.